Taro (Colosia esculenta) Leaves Extract Inhibits Streptococcus mutans ATCC 31987 - Ayu Nala El Muna Haerussana; Angreni Ayuhastuti; Siti Fira Yuniar; Hana Alifah Bustami; Widyastiwi Widyastiwi (Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Dental caries was the most common disease in both adults and children. Streptococcus mutans is the main bacteria causing plaque formation and was the initiator of dental caries. Antibacterials derived from plants can be used to prevent plaque formation. Taro (Colosia esculenta) has been used in traditional medicine. Antibacterial compounds have been discovered in taro leaves. This study aimed to determine the ability of C. esculenta leaf ethanol extract to inhibit the growth of S. mutans ATCC 31987. Simplicia preparation, extract preparation, and phytochemical screening was carried out. Then, the antibacterial activity test was performed using the disc diffusion method to determine the zone of inhibition at various concentrations of 10, 20, 30, 40, 50, 60 dan 70%. Colosia esculenta leaf ethanol extract contains alkaloids, flavonoids, triterpenoids, and saponins, and produces an inhibition zone at each concentration variation. Very strong antibacterial activity was produced at a concentration of 70% at 21.11±0.46 mm, which was higher than the positive control.